The comparison of attenuation factor of 99mTc and 153Sm radionuclides in planar image using Mediso InterViewTM XP and ImageJ - Adni Ahyani; Syarifatul Ulya; Muzilman Muslim; Prasetya Widodo; Nur Rahmah Hidayati; Heru Prasetio (Journal of Medical Physics and Biophysics, 2023)
Planar imaging quantification is a method in internal dosimetry studies that is needed in the preparation and post-therapy evaluation stages. The attenuation factors are needed in Conjugate View Method to obtain accurate image quantification results. In nuclear medicine installation, the high workload of integrated software slows the quantification process, so it is necessary to advance alternative software that is portable and has high accuracy. This study aims to compare the result of attenuation factors using InterViewTM XP and ImageJ plug-in software. The study was conducted by observing attenuation of 99mTc and 153Sm, which have 1, 2, 4, and 25 mCi activities on water slabs phantom with thickness variations of 1–10 cm using a Mediso Anyscan S equipped with Low-Energy High-Resolution collimator. Radionuclides activity measurement was performed using a dose calibrator. The energy window of each radionuclide is adjusted to the spectrum range in the gamma camera software. Image quantification was executed with InterViewTM XP and ImageJ plug-in software. The attenuation factor is obtained by plotting a graph between count versus slab thickness. Analysis result using InterViewTM XP and ImageJ software sequentially is 0.140 ± 0.007 cm-1, 0.140 ± 0.009 cm-1 (99mTc), and 0.128 ± 0.004 cm-1, 0.128 ± 0.004 cm-1 (153Sm) at activity range 1–25 mCi. The result of Paired Samples t-test between ImageJ towards integrated InterViewTM XP software shows that the value of Significance (2-tail) > α; thus, H0 is accepted. It is concluded that ImageJ software is quite accurate in determining the value of attenuation factors.